Admission High-Sensitivity Cardiac Troponin T as an Independent Predictor of 28-Day Mortality in Adult Sepsis: A Prospective Cohort Study - Dr Basavaraj G Yatanoor; Dr Sachin Patil; Dr G B Doddamani, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Sepsis remains a leading cause of critical-care mortality. Mounting evidence suggests that biomarkers of myocardial injury may refine risk-stratification. Methods: This is a prospective observational study of 120 adults with Sepsis-3 who were recruited in a tertiary intensive-care unit. Patients were measured within 6 h of admission in the authors measured high-sensitivity cardiac troponin-T (hs-cTnT), creatine-kinase MB (CK-MB) and lactate-dehydrogenase (LDH) and re-evaluated the outcomes after 28 days. Organ failure was determined by way of SOFA (Sequential Organ Failure Assessment) score. Results: There was a significantly higher median hs-cTnT in non-survivors (n = 39, 32.5 %) (0.202 ng mL 1) in comparison to those that survived (0. 048 ng mL 1; p < 0.001). The same tendency was seen with CK-MB and LDH. hs-cTnT was strongly correlated with SOFA ( 28 = 0.78, AUC of 28 days mortality was 1.00 with an optimal cut-off of 0.10 ng mL 1 delivering 97 % sensitivity/99 % specificity. Another excellent discrimination was apparent in CK-MB (AUC = 0.96) and LDH (AUC = 0.99). Multivariable modelling substantiates hs-cTnT as the overwhelming predictor after being adjusted to age, sex and SOFA. Conclusion: Early elevation of cardiac enzymes—particularly hs-cTnT—portends poor short-term prognosis in sepsis and may complement clinical scores.